'"Asexual" Isn't Who I Am': The Politics of Asexuality. (June 2018) - Dawson, Matt; Scott, Susie; McDonnell, Liz
Some literature on asexuality has claimed that it is inherently radical and contains the potential for resistance. Unfortunately, this literature has tended to be unempirical, has imagined asexuality as a disembodied entity, and has marginalised the multiple identities held by asexual people. This article, inspired by Plummer's critical humanist approach, seeks to explore how individuals understand their asexuality to encourage forms of political action in the areas of identity, activism, online spaces, and LGBT politics. What we found was a plurality of experiences and attitudes with most adopting a pragmatic position in response to their social situation which saw large-scale political action as irrelevant. We conclude by reflecting on what these results mean for those who see asexuality as potentially radical.